1991
DOI: 10.1200/jco.1991.9.9.1609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of autologous bone marrow infusion on hematopoietic recovery after high-dose cyclophosphamide, etoposide, and cisplatin.

Abstract: Because of potential tumor contamination and inadequacy of current purging technique of bone marrow in patients with solid tumors, we investigated an alternative approach to high-dose therapy without autologous bone marrow (ABM) infusion. Three levels of nonmyeloablative doses of cyclophosphamide 4.5 to 5.25 g/m2, etoposide 750 to 1,200 mg/m2, and cisplatin 120 to 165 mg/m2 (CVP) were administered to patients with metastatic solid tumors. Patients were randomized to ABM (n = 46) or no-ABM (NABM) (n = 46) infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Patients who achieved a complete response after ifosfamide and mitoxantrone went on to consolidation BEAM and stem cell rescue. Patients who achieved a Downloaded by [University of Otago] at 08:17 07 October 2015 partial response to the ifosfamide and mitoxantrone received a first intensification with cyclophosphamide, etoposide, cisplatin (CVP) [19][20][21] with infusion of half of the collected stem cells, followed by a second consolidation cycle with BEAM and infusion of the remaining stem cells. At any time, patients with progressive disease were taken off study.…”
Section: "Hatment Plan Patientsmentioning
confidence: 99%
“…Patients who achieved a complete response after ifosfamide and mitoxantrone went on to consolidation BEAM and stem cell rescue. Patients who achieved a Downloaded by [University of Otago] at 08:17 07 October 2015 partial response to the ifosfamide and mitoxantrone received a first intensification with cyclophosphamide, etoposide, cisplatin (CVP) [19][20][21] with infusion of half of the collected stem cells, followed by a second consolidation cycle with BEAM and infusion of the remaining stem cells. At any time, patients with progressive disease were taken off study.…”
Section: "Hatment Plan Patientsmentioning
confidence: 99%
“…9 Jennis and colleagues reported on 80 patients who underwent C 5 g/m 2 , E 1500 mg/m 2 , and P 120 mg/m 2 plus G-CSF. 10 In a median of two apheresis procedures this regimen yielded excellent quantities of CD34 + cells (median of 15.8 ϫ 10 6 /kg) with efficient hematopoietic engraftment.The doses we chose were higher than those studied by Schwartzberg et al 8 and Demirer et al 9 in an attempt to improve anti-cancer effect, but slightly lower than those reported by other investigators [4][5][6]10 in order to avoid thrombocytopenia at the time of apheresis. We observed that DICEP and G-CSF seemed to mobilize ABSC more effectively than our previous mobilization regimens.…”
mentioning
confidence: 91%
“…The doses we chose were higher than those studied by Schwartzberg et al 8 and Demirer et al 9 in an attempt to improve anti-cancer effect, but slightly lower than those reported by other investigators [4][5][6]10 in order to avoid thrombocytopenia at the time of apheresis. We observed that DICEP and G-CSF seemed to mobilize ABSC more effectively than our previous mobilization regimens.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The rationale for delaying the initiation of G-CSF is that late-committed neutrophilic progenitors responsive to G-CSF are not yet formed immediately after PBSCT, 44,45 making the early G-CSF treatment futile. With this in mind, several studies have analyzed the optimal time to start G-CSF after autologous PBSCT.…”
Section: Trivedi Et Almentioning
confidence: 99%